2009
DOI: 10.1002/cmdc.200800296
|View full text |Cite
|
Sign up to set email alerts
|

NG‐Acylated Aminothiazolylpropylguanidines as Potent and Selective Histamine H2 Receptor Agonists

Abstract: The bioisosteric replacement of the guanidino group in arpromidine-like histamine H(2) receptor (H(2)R) agonists by an acylguanidine moiety is a useful approach to obtain potent H(2)R agonists with improved oral bioavailability and blood-brain barrier penetration. Unfortunately, the selectivity of such N(G)-acylated imidazolylpropylguanidines for the H(2)R is poor, in particular versus histamine H(3) (H(3)R) and H(4) receptors (H(4)R). This drawback appears to depend on the "privileged" imidazolylpropylguanidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 27 publications
(32 reference statements)
3
61
0
Order By: Relevance
“…[14,16] N'-Substituted N-tert-butoxycarbonyl-S-methylisothioureas 16-27: DIPEA (4.0 mmol) in CH 2 Cl 2 (10 mL) was added to a solution of N-tert-butoxycarbonyl-S-methylisothiourea (0.76 g, 4.0 mmol) in 10 mL anhydrous CH 2 Cl 2 . A solution of the respective acylating agent (4.0 mmol) in CH 2 Cl 2 (5 mL) was added, and the reaction mixture was shaken overnight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14,16] N'-Substituted N-tert-butoxycarbonyl-S-methylisothioureas 16-27: DIPEA (4.0 mmol) in CH 2 Cl 2 (10 mL) was added to a solution of N-tert-butoxycarbonyl-S-methylisothiourea (0.76 g, 4.0 mmol) in 10 mL anhydrous CH 2 Cl 2 . A solution of the respective acylating agent (4.0 mmol) in CH 2 Cl 2 (5 mL) was added, and the reaction mixture was shaken overnight.…”
Section: Methodsmentioning
confidence: 99%
“…[15] Furthermore, in the field of histamine receptor agonists, acylguanidines were identified as bioisosteres of guanidines or mimics of amino groups. [10,14] Receptor mutagenesis and molecular modeling studies revealed that the guanidino group of the Y 1 R antagonistic (R)-argininamide BIBP3226 and its N G -acylated analogues interact with a highly conserved Asp residue in TM6 of the Y 1 R. [32] In the Y 2 R an Asp residue at the corresponding position is crucial for agonist binding, but does not substantially contribute to binding of BIIE0246. [33,34] Other residues were found to be important for direct antagonist interactions, such as Tyr in TM2 and Leu in TM5.…”
Section: Acylguanidines As Less Basic Bioisosteric Replacements For Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity problem was solved by bioisosteric replacement of the imidazol-4-yl with a 2-aminothiazol-5-yl residue, optionally bearing a 4-methyl substituent as in amthamine. 2-Aminothiazoles, such as UR-BIT24, are about equipotent to the corresponding imidazoles at the H 2 receptor but devoid of noteworthy activities at H 1 receptors, H 3 receptors and H 4 receptors (Kraus et al, 2009).…”
Section: E H 2 Receptor-selective Ligandsmentioning
confidence: 99%
“…The K d value determined from saturation binding was applied for the calculation of K i values by means of the Cheng-Prusoff equation. [45] As summarized in Table 5, the hH 2 R binding affinity of the agonists histamine (K i = 534 nm), amthamine (K i = 244 nm), URBit24 [46] (K i = 7.1 nm) and UR-AK480 [47] (K i = 1.9 nm), and of the antagonists famotidine (K i = 136 nm), ranitidine (K i = 1730 nm), BMY 25368 (K i = 19 nm) and iodoaminopotentidine (K i = 0.31 nm) were consistent with reported data from functional and binding experiments. [40,48] The K i value of 24 a on the hH 2 R (28 nm), determined by competition binding experiments with the labeled analogue 24 b, corresponds very well to the K d value of compound 24 b (31 nm), and the data for the rat and guinea H 2 R species orthologues were in the same range (K i values: 16 and 43 nm, respectively).…”
Section: Pharmacologymentioning
confidence: 99%